Chapter 6 How liberating is liberation technology? - Angus, Simon (Taylor & Francis, 2023)
It has been a decade since Diamond's seminal and sober work on the possibilities of 'liberation technology' to 'expand political, social and economic freedom' (Diamond 2010). Since that time, the Arab supernova has electrified Twitter's supporters, Russian paws and exquisite Cambridge algorithms have lent on the scales of a presidential campaign via social media, and China has amassed the data and technology to control its citizenry with cold efficiency. So what of liberation technology? What do we know about its impact on political participation, expression and freedom? In this chapter I review the promise and complexities of the pursuit of freedom via liberation technology. Tracing powerful forces that have darkened liberation technology's initial promise, I look specifically at the complexities of both access to, and activism via, social media, showing how simple and naïve characterisations of its role in political engagement are misplaced. Whilst these results would appear to suggest that oppressive regimes have already snuffed out the promise of technology to support wider freedoms, recent theorising suggests that a pathway to freedom and prosperity has been opened where both the state and society have equal strength in the technology of accountability, information, and coordination, co-investing in each other's capacity.